CONGENITALLY MISSING OF THE MAXILLARY LATERAL INCISOR: ORTHODONTIC CLOSURE OF THE SPACE - Daniela Anistoroaei; Dror Aizenbud; Georgeta Zegan; Cătalina Iulia Săveanu; Vasilica Toma; Loredana Golovcencu (Romanian Journal of Oral Rehabilitation, 2023)
Aim of the study: The aim of the study the aim of the study was to analyze the effectiveness of orthodontic space closure treatment in patients with congenitally missing of upper lateral incisors (CMULI). Materials and methods. The study was carried out on a group of 25 patients with CMULI aged between 7-25 years (average age 14.6 years), who presented themselves for CMULI treatment. Fixed orthodontic appliance, protraction facial mask and class III elastics were applied to all patients. The cephalometric radiographs before and after treatment were analyzed to observe if the application of the orthodontic appliance produces dento-alveolar retrusion and the statistical correlations between the studied parameters were analysed. Results. The statistical analysis of the studied variables showed that there are no statistically significant correlations between the initial and final cephalometric values, obtained after the orthodontic treatment. Conclusions The association of fixed orthodontic appliances together with protraction facemask and class III elastics represents an effective method of treatment of congenitally missing of upper lateral incisor.